Appropriate use of single-dose injectable aripiprazole lauroxil in the treatment of schizophrenia - Rachael C. Davis, BS; Jianing Xu, MS; Daniel B. Hall, PhD; Xianyan Chen, PhD; Michaelyn M. Moretz; Henry N. Young, PhD; Joshua Caballero, PharmD, BCPP, FCCP (Mental Health Clinician)
Introduction Single-dose injectable aripiprazole lauroxil (SDIAL) is used with long-acting injectable (LAI) aripiprazole lauroxil in the treatment of schizophrenia. SDIAL can be used to either initiate treatment or supplement during maintenance when follow-up doses are not given within labeling recommendations. The primary objective was to determine the usage and appropriateness of SDIAL between the initiation and the maintenance supplementation use in a Medicaid database. The secondary objective was to determine the overall associated costs with the potentially inappropriate use of LAI aripiprazole lauroxil. Methods International Classification of Diseases, 10th edition codes were used to identify adult patients with schizophrenia and related disorders (18-64 years) who received SDIAL and/or LAI aripiprazole lauroxil between 2018 and 2020 using MarketScan Medicaid databases. The appropriateness of SDIAL was determined by package insert labeling timelines for treatment initiation and maintenance supplementation. Two authors independently reviewed each SDIAL claim for appropriateness. Descriptive statistics were used to analyze the data. Results After excluding possible billing errors, a total of 582 claims were identified for SDIAL. Of these, 21% were potentially inappropriate, with a higher proportion occurring during the maintenance phase. Overall, potential inappropriate use resulted in costs over $307 000. Discussion It appears that prescribers should be better educated on the appropriate use of SDIAL during maintenance supplementation.